Inflammatory and redox reprogramming of macrophages by HIV cell-to-cell transmission inhibits bone resorption capacity - Sviercz, Franco A.; Jarmoluk, Patricio; Russo, Constanza; López, Cynthia Alicia; Freiberger, Nicole; Cevallos, Cintia; Delpino, M. Victoria; Quarleri, Jorge (Frontiers in Immunology, 2025)
IntroductionPeople with HIV experience bone loss, but how viral spread perturbs osteoclastogenesis remains unclear. We asked whether cell-to-cell transmission of HIV from infected CD4+ T cells to macrophages reprograms precursors and impairs osteoclast differentiation.MethodsWe co-cultured Jurkat cells infected with R5- or X4-tropic HIV with human monocyte-derived macrophages (M0/M1/M2) and quantified infection (p24/GFP), inflammasome activation and death (IL-1β, AnnexinV/7-AAD, z-YVAD), adhesion molecules/tetraspanins (ICAM-1, LFA-1, CD9/CD63/CD81), mROS (MitoSOX, NAC), polarization markers/cytokines, and osteoclastogenesis (TRAP, actin ring, CD51/61, adhesion, bone resorption).ResultsR5 HIV infected M0>M2>M1 macrophages via contact, sustaining p24 release across differentiation and reducing TRAP+ osteoclasts and resorption. HIV-exposed macrophages showed inflammasome-linked death and IL-1β induction; contact enhanced Mf–T conjugates and upregulated ICAM-1/LFA-1 and tetraspanins. HIV-infected T cells displayed pro-inflammatory TNF-α/IFN-γ profiles, skewing macrophages toward M1-like states. Jurkat-derived ROS promoted conjugates and mROS accumulation in macrophages, while NAC reduced contact and oxidative imbalance. Nevirapine partially restored osteoclastogenesis and revealed contact-associated drug insensitivity.DiscussionThe effects scaled with the proportion of infected T cells. HIV cell-to-cell spread induces inflammatory and redox reprogramming in macrophage precursors that blocks osteoclast differentiation and function, offering testable targets (inflammasome, adhesion, ROS) to protect bone in HIV.